2012
DOI: 10.1111/j.1750-3841.2012.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Quantitative PCR and Western Blot Detecting CP4‐EPSPS Component in Roundup Ready Soy Plant Tissues and Commercial Soy‐Related Foodstuffs

Abstract: The combination of quantitative PCR (qPCR) and western blot was used to detect cp4-epsps gene and its protein product in different Roundup Ready soy (event 40-3-2) plant tissues and commercial soy-containing foodstuffs. The foods included those of plant origin produced by different processing procedures and also some products containing a combination of both meat and plant protein concentrates. This study indicated that the combination of DNA- and protein-based methods would supplement each other for genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…To test its usefulness in analyzing GMOs, the transgenic soybeans called Roundup® Ready (RR) 1 and 2 developed by the Monsanto Corporation were analyzed by using this QuantStudio™ 3D Digital PCR System. Many studies have been conducted on the RR1 soybean, mainly using PCR-based methods to detect and/or quantify the transgene, e.g., [37]- [44]. Recently, detection and quantification of RR2 using digital PCR were also reported [34].…”
Section: Introductionmentioning
confidence: 99%
“…To test its usefulness in analyzing GMOs, the transgenic soybeans called Roundup® Ready (RR) 1 and 2 developed by the Monsanto Corporation were analyzed by using this QuantStudio™ 3D Digital PCR System. Many studies have been conducted on the RR1 soybean, mainly using PCR-based methods to detect and/or quantify the transgene, e.g., [37]- [44]. Recently, detection and quantification of RR2 using digital PCR were also reported [34].…”
Section: Introductionmentioning
confidence: 99%
“…CP4-EPSPS was derived from the soil bacterium Agrobacterium sp. Strain CP4 and the enzyme activity of CP4-EPSPS could not be inhibited by glyphosate due to weak binding affinity, resulting in increased tolerance to glyphosate in transgenic plants expressing this gene ( Franz et al, 1997 ; Guicheney et al, 2009 ; Xiao et al, 2012 ). GAT encodes an N-acetyltransferase for acetylation of glyphosate, which is the basis of a new mechanism of glyphosate tolerance in GM plants ( Castle et al, 2004 ; Siehl et al, 2005 , 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that high temperature and/or pressure lead to serious DNA degradation and significantly reduce the level of detectable DNA. Xiao et al (2012) used polymerase chain reaction (PCR) and Western blotting methods to evaluate the degradation of the CP4-EPSPS gene and protein in various bean foodstuffs, such as dried bean curd crust and deep-fried bean curd, and reported inconsistent results between the two detection techniques. Previous studies focused mainly on the degradation of exogenous genes in transgenic soybean, transgenic corn, and transgenic maize (Gryson, 2010), and little information is available on exogenous Bt genes or Bt proteins in transgenic rice.…”
Section: Introductionmentioning
confidence: 99%